Dampak Perkembangan Pariwisata Terhadap Lingkungan Di Pantai Cacalan Banyuwangi - Oktaviana, Febi; Andini, Nila Utary; Aprilia, Della; -, Kanom (JURNAL DESTINASI PARIWISATA, 2023)
The tourism industry is crucial to the success of initiatives to enhance government income. The tourist industry in Indonesia needs to grow since the country is home to both breathtaking natural beauty and cultural variety. Banyuwangi Regency is one of the regions helping to boost the country's GDP by attracting more tourists. The methodology of this study is qualitative. Qualitative research is a methodology that sheds light on a specific social situation by an accurate description of reality, shaped by words derived from appropriate data collection and analytic methodologies used to information gathered in natural settings. Data is obtained from primary data and secondary data. The purpose of this article is to determine the impact of tourism on the environment in Cacalan Beach in the management and development of Cacalan Beach. The results obtained are known first, the development of tourism has been very good in terms of aspect 5 A. Second, facilities and infrastructure have developed. Third, in its development, public awareness is still not optimal. Fourth, there is a clean tourism program that can preserve nature. Keywords: Tourism Development, Impact, environment